1975
DOI: 10.1007/bf01070754
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal fluid and electrolyte secretion in carcinoid syndrome

Abstract: To evaluate the pathogenesis of the diarrhea of carcinoid syndrome, triple-lumen jejunal-perfusion studies were performed in three patients with carcinoid syndrome and diarrhea and eleven control subjects. In contrast to the net absorption observed in the control subjects during perfusion with an isotonic mannitol-saline solution, net secretion occurred in two of the three carcinoid-syndrome patients. Glucose absorption and glucose-stimulated fluid absorption were normal in the carcinoid-syndrome patients. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Previous studies have shown that 5-HT administration in vivo induces Cl Ϫ secretion in the rabbit small intestine (31) and acts as a mediator of diarrhea in patients with carcinoid syndrome associated with a net secretion of water and electrolytes (32). Therefore, these studies suggest an important role of 5-HT in modifying electrolyte transport process that could involve either stimulation of Cl Ϫ secretion or a decrease in Na ϩ and Cl -absorption.…”
Section: -Htmentioning
confidence: 87%
“…Previous studies have shown that 5-HT administration in vivo induces Cl Ϫ secretion in the rabbit small intestine (31) and acts as a mediator of diarrhea in patients with carcinoid syndrome associated with a net secretion of water and electrolytes (32). Therefore, these studies suggest an important role of 5-HT in modifying electrolyte transport process that could involve either stimulation of Cl Ϫ secretion or a decrease in Na ϩ and Cl -absorption.…”
Section: -Htmentioning
confidence: 87%
“…14,15 Donowitz and Binder 17 have described increased intestinal secretion in patients with carcinoid diarrhea, which will also contribute to diarrhea. Therefore, these factors rather than abnormal rectal mechano-sensory function are likely the major causes of carcinoid diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…shown that patients with carcinoid diarrhea have intestinal hypersecretion 17 and faster than normal transit through the small intestine and the colorectum. [14][15][16] However, it is well known from other patient groups that frequent bowel movements may be associated with rectal hypersensitivity and increased rectal tone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 However, evidence is accumulating on the importance of other mediators such as 5-hydroxytryptamine (5-HT) present in enterochromaf®n cells and acting through receptors in the enteric nervous system. 3 5-HT is known to be an intestinal secretagogue, 4,5 and raised concentrations of 5-HT are found in carcinoid syndrome 6 and in diarrhoea associated with morphine withdrawal. 7 The possibility that 5-HT may also be involved in CT-induced secretion was SUMMARY Background: 5-hydroxytryptamine type 3 receptor antagonists have been shown to reduce¯uid and electrolyte secretion or promote absorption in experimental models of small intestinal secretion.…”
Section: Introductionmentioning
confidence: 99%